2021
DOI: 10.1155/2021/8882505
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Stem Cell Therapies for Articular Cartilage Regeneration

Abstract: Injury of articular cartilage can cause osteoarthritis and seriously affect the physical and mental health of patients. Unfortunately, current surgical treatment techniques that are commonly used in the clinic cannot regenerate articular cartilage. Regenerative medicine involving stem cells has entered a new stage and is considered the most promising way to regenerate articular cartilage. In terms of theories on the mechanism, it was thought that stem cell-mediated articular cartilage regeneration was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 216 publications
(114 reference statements)
1
37
0
Order By: Relevance
“…Currently, the potential mechanisms of stem cells in articular cartilage regeneration can be divided into two main categories: the "differentiation theory" and "paracrine theory" [33]. Differentiation theory is an approach to articular cartilage regeneration therapy in which stem cells directly differentiate into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the potential mechanisms of stem cells in articular cartilage regeneration can be divided into two main categories: the "differentiation theory" and "paracrine theory" [33]. Differentiation theory is an approach to articular cartilage regeneration therapy in which stem cells directly differentiate into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the injured cartilage tissue, activated chondrocytes increase the production of cartilage, degrading catabolic enzymes, proinflammatory cytokines, and oxidative stress inducers, which induces the degradation of the cartilage matrix and chondrocyte apoptosis or necrosis via activation of the NF-κB pathway, leading to irreversible articular damage and functional impairment [ 149 , 150 ]. Standard surgical clinical techniques cannot regenerate the articular cartilage [ 151 ]. Due to the lack of blood vessels, nerves, and lymphatic vessels and the restriction of the dense extracellular matrix (ECM) on cartilage cells, the post-injury self-healing ability of the articular cartilage is very limited [ 148 , 151 , 152 ].…”
Section: Dental Mscs-cm In Tissue Regenerationmentioning
confidence: 99%
“…Standard surgical clinical techniques cannot regenerate the articular cartilage [ 151 ]. Due to the lack of blood vessels, nerves, and lymphatic vessels and the restriction of the dense extracellular matrix (ECM) on cartilage cells, the post-injury self-healing ability of the articular cartilage is very limited [ 148 , 151 , 152 ]. A new approach in cartilage-injury tissue therapy is regenerative medicine [ 148 , 151 ].…”
Section: Dental Mscs-cm In Tissue Regenerationmentioning
confidence: 99%
“…Studies have shown that pretreatment is an effective way to improve the ability of cells to resist adverse microenvironments. Stem cell pretreatment can improve cell survival and differentiation potential, regulate immune response, inhibit fibrosis, and enhance cell secretion of anti-inflammatory factors [ 50 ]. Therefore, a stem cell pretreatment strategy has also received a lot of attention in the field of releasing EVs to treat OA.…”
Section: Cell Pretreatment Strategymentioning
confidence: 99%